Pemberdayaan Peternak Pada Suku Akit Melalui Pemanfaatan Bahan Baku Pakan Lokal Tepung Biji Karet Fermentasi Sebagai Ransum Pellet Puyuh Petelur - Anwar Efendi Harahap; Oksana Oksana; Bakhendri Solfan; Irsyadi Siradjuddin (Lembaga penelitian dan pengabdian kepada masyrakat, 2020)
The Akit tribe is the original tribe of Rupat Island who is used to living hunting and gathering. The Akit tribe is one of the remote indigenous communities (KAT) in Riau Province. This service aims to utilize and process rubber seeds with pellet technology as animal feed for laying quail rations as an effort to improve the welfare of the community. The service method is the Community Based Research (CBR) method, which is a method where the community takes part in this research and service process. The results show that community service activities generate 80 - 90% feedback from the community, even though most people have low levels of education but still easily understand the material. Furthermore, the ration consumption during quail maintenance was 19.65 - 22.01%, the weight of quail eggs was 6.66 - 8.35% and the ration conversion was 2.36 - 3.43. The conclusion of this service is that fermented pellet ration up to 6% of rubber seed flour be used as laying quail feed with the community based research (CBR) service model to motivate breeders to increase their business in raising quail in a sustainable